Fast cation exchange of layered sodium transition metal oxides for boosting oxygen evolution activity and enhancing durability. Issue 16 (16th April 2020) - Chu, Shiyong; Guan, Daqin; Sun, Hainan; Fei, Liangshuang; Hu, Zhiwei; Lin, Hong-Ji; Weng, Shih-Chang; Chen, Chien-Te; Ran, Ran; Zhou, Wei; Shao, Zongping
Abstract : An ex situ ultra-fast cation exchange strategy to develop superior OER electrocatalysts with outstanding catalytic performance is developed. Abstract : Cost-effective electrocatalysts with high activity and long durability for the oxygen evolution reaction (OER) are key to water splitting and rechargeable metal–air batteries. Here, we report the development of a superior OER electrocatalyst with outstanding activity, favorable durability, and stable particulate morphology based on an ex situ ultra-fast cation exchange strategy that can result in fine tuning of the atom arrangement inside the oxide lattice, thus optimizing the electrocatalytic performance. O3-phase NaCo0.8 Fe0.2 O2 (O-NCF) is selected as the starting material, and the sodium in the oxide lattice is rapidly exchanged (several minutes) with hydronium ions (H3 O + ) in an acidic solution. The as-derived structure fine-tuned sample displays excellent OER performances in alkaline media with an ultra-low overpotential of only 234 mV at 10 mA cm −2 in oxide-based electrocatalysts and an ultra-small Tafel slope of 34 mV dec −1 . The exchange of H3 O + with Na + does not affect the oxidation state of cobalt and iron cations inside the oxide lattice, while protons in the inserted H3 O + promote the formation of the hydroxyl group to improve activity. As a general strategy, such cation exchange strategy can also be applied to many other layered sodium transition metal oxides.